The Effect of Work Discipline, Compensation and Work Motivation on Employee Performance at PT Musi Hutan Persada - Ahmad Maqom Mahmuda; Marlina Widyanti; Muhammad Yusuf; Muhammad Ichsan Hadjri (Journal of Management Economic and Financial, 2024)
This research was conducted with the aim of determining the influence of work discipline, compensation and work motivation on employee performance at PT Musi Hutan Persada. The population in this research is all employees at PT Musi Hutan Persada totaling 1741 employees in 2024. The sampling technique in this research is using a total sampling technique, because in this research the author took all employees at PT Musi Hutan Persada in 2024 as many as 120 people employees as a sample. The results of multiple linear regression analysis show that work discipline, compensation and work motivation have a positive and significant effect on employee performance. Work discipline, it is hoped that clear and transparent sanctions will be applied to all employees. Compensation, it is hoped that salaries can be adjusted again based on the company's income and profits based on the position held by the employee. Work motivation is expected for PT Musi Hutan Persada to form team members. Where team members need to be adjusted based on education, skills and abilities to be able to carry out the job.